THE NEED OF FAMILY LIFE EDUCATION IN MACEDONIA: A DEBATE (Annual of the Faculty of Philosophy in Skopje, 2016)
The answer to the question whether there are grounds or needs for family life education in Macedonia is positive. General perceptions show that knowledge transfer "from generation to generation" is insujficient for family members to take over and successfully play the roles and responsibilities of family life.All members of the family should, in a certain way be involved in family life education, thus contributing to the well-being and development of families.The level of competence and knowledge might be adjusted to the audience structure, the conditions, group-targets, and chosen theme entirety, and might vary from typical types of training and education of pre-school children, through seminars with basic and medium level content size and structure, up to university academic studies and scientifically grounded and applicable research, dedicated to family life education.
Keywords: FAMILY; FAMILY LIFE; EDUCATION; VALUES; GOALS OF EDUCATION; FORMSAND MEDIA EDUCATION FOR FAMILY LIVING